Effective Resource Allocation in Parallel Quantum-Chemical Calculations - Mazur, Grzegorz; Makowski, Marcin; Brela, Mateusz (Computing and Informatics, 2012)
Key factors affecting the parallel efficiency of archetypical quantum-chemical calculations are discussed. Effective load balancing schemes are proposed. Introduction of the memory affinity to the balancing process is shown to result in super-linear scaling.